Study of supplementary controls for embedded HVDC links in a AC power system - Avila, Hector Armando (My University, 2008)
This document reports a comprehensive study of supplementary control schemes for HVDC inter‐ties parallel to AC transmission lines in order to reduce electromechanical inter‐area oscillations employing a suitable two‐area power system. The study includes design procedure and an extensive analysis based upon time domain detailed simulations, developed using PSCAD/EMTDC. Results obtained from two‐area power system show how the control over the HVDC inter‐tie effectively reduces the electromechanical inter‐are oscillations. The supplementary outer control loop of the HVDC link, suitably designed, permits to increase the damping ratio of the system to a safe value, which can not be attained solely using power system stabilizers. Power modulation through the HVDC link effectively reduces electromechanical inter‐area oscillations under a wide range of composite static load characteristics. Response is however limited by the value of the voltage index for active power; the compensation loop is functional only when this index is greater than one. The effectiveness of the supplementary control scheme is barely affected by the value of the voltage index for reactive power; these results reduce the modeling considerations of the reactive power characteristics, which in practical circumstances are more variable and depending on several and sometimes unknown factors.
Keywords: Elkraftteknik; Electric power engineering